REFLECTION OF THE ACQUIRED FORMAL EDUCATION OF TEACHERS FROM THE PERSPECTIVE OF THEIR VALUE ORIENTATION - Kropáč, Jiří; Koribská, Iva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article deals with the value orientation of teachers in the Czech Republic, who attempt to extend their formal education in the process of lifelong learning. The quality of the teacher directly influences the quality of the educational process, therefore the qualification of teachers has become the front theme of the international organisations. Lifelong Learning Centres as parts of the universities offer the programmes for teachers to extend their formal qualification. The primary aim of the article is to analyse teachers’ value orientation reflected by the formal education.